Chronic toxicity of inhaled thymol in lungs and respiratory tracts in mouse model - Kevin Xie; Donald P. Tashkin; Mary Z. Luo; Jack Y. Zhang (Wiley, 2019)
Abstract Epinephrine HFA (Primatene® Mist) is a newly formulated asthma metered dose inhaler developed to replace the previous Primatene® Mist CFC. The formulation of Epinephrine HFA contains thymol, a substance recognized to be safe by the FDA. Although the content of thymol contained in Epinephrine HFA is much lower compared to many common foods and medications available, there are no known nonclinical data about the chronic toxicity of thymol through inhalation. Two sequential 6‐month studies of identical design were conducted to assess the chronic toxicity of inhaled thymol in mice. Four treatment groups, (a) Air; (b) vehicle control; (c) Article‐1 (thymol 0.1%); and (d) Article‐2 (thymol 0.5%) were assessed in 128 mice for 26 weeks. The mice were sacrificed at the end of the treatment period and a histopathologic evaluation was performed with respect to lungs, bronchial lymph nodes, nasal passages/nasopharynx, and trachea. Forty‐five pathologic assessment parameters (PAPs) were evaluated. In total, 5591 data points from 487 mouse organs were assessed. Chronic toxicity index was calculated for 16 PAPs that had multiple histopathologic abnormal observations. The t tests were conducted for these 16 PAPs (Articles‐1 and 2 versus Air and vehicle control, respectively), and all P‐values were greater than .05 indicating no significant differences between all treatment groups. An evaluation was also conducted for 25 PAPs that had only a very small number of pathologic abnormalities. No significant differences for chronic toxicity were found when comparing mice under long‐term repeated exposure of high doses of inhaled thymol and mice that inhaled no thymol.